Application of aqueous two phase systems based on polyethylene glycol and sodium citrate for the recovery of phenolic compounds from Eucalyptus wood - Xavier,Lucía (Universidad del Bío-Bío, 2015)
This paper proposes an alternative way to intensify the exploitation of Eucalyptus wood wastes before valorisation for energy production. An aqueous two-phase system (ATPS) based on PEG 2000 and sodium citrate was investigated for the recovery of phenolic compounds that could act as natural antioxidants for applications including cosmetics, pharmaceuticals, food additives and other industrial applications. The influence of the tie line length (TLL) (26,1-46,1%), extraction temperature (25-65ºC), extraction time (90-390 min) and phase settlement time (1-8 h) were studied. Phenolic compounds were concentrated preferentially in the PEG-rich phase. A partition coefficient of 38 and a total phenols yield of 1,29 mg gallic acid equivalent/100 mg wood dry basis were obtained under the operational conditions selected: TLL, 46,1%, temperature 65ºC, extraction time 90 min and settlement time 1 h. Analysis of the extracts by RP-HPLC-ESI-TOF confirmed the presence of various phenolic compounds with demonstrated antioxidant activity: monogalloyl glucose, (-)-gallic acid, ellagic acid and quercetin 3-O-rhamnoside.